Managing personal learning environments: the voice of the students - Costa, Fernando Albuquerque (2012)
The main purpose of this paper is to contribute to a better understanding of the kind of educational work to be done with higher education students (undergraduate) in order to encourage them to create and use personal learning environments (PLEs) as a strategy for learning (Attwell, 2007). Based on our current classroom work with students of the 2nd year of a degree in Education and mainly using the functionalities of the Ning system (Copyright © 2010 Ning, Inc.), as well as other tools available on the Internet, we tried to implement a strategy based not only on the presentation of content by the teacher, but also on the recognition of the importance of student’s leadership in the organisation and management of their own learning. Therefore, in addition to face-to-face lectures, we tried to extend the discussion outside the classroom walls using the different services offered by Ning, proposing to integrate the work done by students in their individual evaluation (50% of the final classification). At the end of the semester we observed evidence of a general difficulty felt by the students, particularly in terms of self-regulation and personal organisation. So we decided to try to understand the problem observed in depth. For the purpose of understanding the nature and the extent of these difficulties, we used a methodology focused on analysis of a questionnaire applied to the students about their perception of the difficulties in managing the learning process and about the strategies used for dealing with those difficulties. Although the students acknowledge that the development of the individual online portfolio in a PLE requires that, for the most part, largely they themselves have to get organised and manage of their own learning (Barrett, 2000; Attwell, 2007), one can see that they do not feel prepared for this, experiencing difficulties in personal organisation, time management and regular participation in the proposed activities. In strategic terms, they value the appraisals and/or suggestions given by the teachers, but do not adopt an attitude of reflection or interaction and sharing with others, as catered for by the platform and its functionalities.